Characterization of a probiotic starter culture with anti-Candida activity for Chinese pickle fermentation. Issue 10 (8th October 2019) - Rao, Yu; Tao, Yufei; Li, Yalin; She, Xiao; Yang, Jiantao; Qian, Yang; Du, Hengjun; Liu, Lei; Xiao, Hang
Abstract : A probiotic starter can be used for Chinese pickle fermentation and the resulting product may be a promising anti- Candida probiotic. Abstract : Probiotic starters for Chinese pickle fermentation were screened from three anti- Candida lactic acid bacteria (LAB). Similar to commercial starters, the candidates Lactobacillus plantarum AT4 and L. plantarum AT28 could acidize the pickle within 10 days. The isolates AT4 and AT28 maintained 6.0–7.0 log cfu ml −1 in the pickle products and their inhibition rates against Candida increased to 83.7% and 92.9% after fermentation, respectively. Only L. plantarum AT4 satisfied the essential probiotic requirements such as tolerance to the gastrointestinal environment (pH 2.0, 0.5% bile salts and 0.5% phenol) and adhesion to Caco-2 cells. The pickle product fermented with L. plantarum AT4 presented comparable levels of lactic and acetic acids, volatile profile and sensory value to the commercial one. The results suggested that L. plantarum AT4 can be used as a probiotic starter for industrial fermentation of Chinese pickle, and the pickled product may be utilized as a promising anti- Candida probiotic.